Samuel Beckett : The Art of Rhetoric - McMillan, Dougald; Harper, Howard M.; Morot-Sir, Edouard (North Carolina studies in the Romance languages and literatures. Symposia, 2019)
Collected essays from a symposium held in April 1974, at the University of North Carolina at Chapel Hill, this volume analyzes Beckett's philosophy, rhetoric, poetry, and novels.